Mutations in PHF8 are associated with X linked mental retardation and cleft lip/cleft palate. Issue 10 (30th September 2005) - Laumonnier, F; Holbert, S; Ronce, N; Faravelli, F; Lenzner, S; Schwartz, C E; Lespinasse, J; Van Esch, H; Lacombe, D; Goizet, C; Phan-Dinh Tuy, F; van Bokhoven, H; et al.
Abstract : Truncating mutations were found in the PHF8 gene (encoding the PHD finger protein 8) in two unrelated families with X linked mental retardation (XLMR) associated with cleft lip/palate (MIM 300263). Expression studies showed that this gene is ubiquitously transcribed, with strong expression of the mouse orthologue Phf8 in embryonic and adult brain structures. The coded PHF8 protein harbours two functional domains, a PHD finger and a JmjC (Jumonji-like C terminus) domain, implicating it in transcriptional regulation and chromatin remodelling. The association of XLMR and cleft lip/palate in these patients with mutations in PHF8 suggests an important function of PHF8 in midline formation and in the development of cognitive abilities, and links this gene to XLMR associated with cleft lip/palate. Further studies will explore the specific mechanisms whereby PHF8 alterations lead to mental retardation and midline defects.